Attentional bias in people with acute versus persistent insomnia secondary to cancer. - Taylor, L; Espie, C; White, C (2003)
This study investigated the role of attentional bias in the development of persistent insomnia. Two groups of people with cancer who developed sleep-onset problems 0-3 months and 12-18 months after diagnosis completed a computerized emotional Stroop task comprising cancer-related and sleep-related word cues and self-complete measures. Both groups demonstrated attentional bias for cancer-related words, but only the persistent insomnia group demonstrated attentional bias for sleep-related words. High levels of presleep cognitive arousal were evident in both groups despite lower levels of psychological distress in the persistent insomnia group. Results suggest that secondary, sleep-related mental preoccupation may inhibit recovery to normal sleep after stress-related acute sleep disturbance. Findings are discussed in relation to current models of insomnia.